Nondrug-related aspect of treating Ekbom disease, formerly known as restless legs syndrome - Mitchell UH (Dove Medical Press, 2011)
Ulrike H MitchellDepartment of Exercise Sciences, Brigham Young University, Provo, UT, USAAbstract: Ekbom disease (EKD), formerly known as restless legs syndrome (RLS) has affected and bothered many people over the centuries. It is one of the most prevalent neurological disorders in Europe and North-America, affecting about 10% of the population. The main characteristics are the strong urge to move, accompanied or caused by uncomfortable, sometimes even distressing, paresthesia of the legs, described as a "creeping, tugging, pulling" feeling. The symptoms often become worse as the day progresses, leading to sleep disturbances or sleep deprivation, which leads to decreased alertness and daytime functions. Numerous studies have been conducted assessing the efficacy of dopaminergic drugs, opioids, and other pharmacologic agents in alleviating EKD symptoms. However, there is also a growing body of evidence demonstrating the effectiveness of nonpharmacologic treatments including life style changes, physical activity programs, pneumatic compression, massage, near-infrared light therapy, and complementary therapies. The working mechanisms behind these alternatives are diverse. Some increase blood flow to the legs, therefore reducing tissue hypoxia; some introduce an afferent counter stimulus to the cortex and with that "close the gate" for aberrant nerve stimulations; some increase dopamine and nitric oxide and therefore augment bio-available neurotransmitters; and some generate endorphins producing an analgesic effect. The advantages of these treatments compared with pharmacologic agents include less or no side effects, no danger of augmentation, and less cost.Keywords: RLS, modalities, massage, intermittent compression, NIR